A case of B-cell acute lymphoblastic leukemia in a child with Down syndrome bearing a t(2;12)(p12;p13) involving ETV6 and biallelic IGH@ rearrangements. Issue 1 (December 2015) - Tirado, Carlos; Shabsovich, David; Kim, Yeun; Traum, Peter; Pullarkat, Sheeja; Kallen, Michael; Rao, Nagesh
Abstract Background Rearrangements involvingETV6 (12p13) are among the most common structural abnormalities in pediatric B-cell acute lymphoblastic leukemia (B-ALL) and involve numerous partner genes. Additionally, the t(8;14)(q11.2;q32), which can result in the placement ofCEBPD (8q11.2) near the regulatory regions ofIGH@ (14q32) and consequent overexpression ofCEPBD, occurs at a higher frequency in individuals with Down syndrome-associated ALL (DS-ALL) compared to both the general and pediatric population. The coexistence of cytogenetically detectableETV6 abnormalities and t(8;14)(q11.2;q32) is a rare occurrence in B-ALL and has only been reported in a single case in the literature. Findings Herein, we present a case of B-ALL in a 9-year old male with Down syndrome in which conventional cytogenetic analysis revealed two reciprocal translocations: a t(8;14)(q11.2;q32) and a t(2;12)(p12;p13). Interphase and metaphase fluorescence in situ hybridization (FISH) analysis using break apart probes confirmed the involvement ofIGH@ andETV6 in these translocations, respectively. Additionally, interphase FISH revealed a clonal subpopulation bearing biallelicIGH@ rearrangements not observed by conventional cytogenetic analysis. Conclusions To the best of our knowledge, this is the first reported case of B-ALL bearing anETV6 translocation with a partner gene on the short arm of chromosome 2 confirmed by FISH. Additionally, it is the second reported case of t(8;14)(q11.2;q32)-ALL bearing a concomitant, cytogenetically detectable abnormality involvingETV6 . This case provides insight into a novel translocation involvingETV6 as well as potentially unique and understudied mechanisms of clonal evolution in pediatric B-ALL.